Comparison of Hospital Mortality, Length of Stay, Renal Recovery, and Needs for Hemodialysis in Acute Kidney Injury (AKI) Patients due to Septic and Non-septic, and Factors Affecting Patients’ Mortality - Marzuki, Mochammad Jalalul; Nursamsu, Nursamsu; Rifai, Achmad (Jurnal Penyakit Dalam Indonesia, 2022)
Introduction. Acute kidney injury (AKI) is a major complication in critically ill patients that affects mortality. Sepsis is a major predisposing factor for AKI and provides a poor prognosis and high mortality rate. Thisstudy aimed toidentifythe difference of hospital mortality, length of stay, renal recovery, and needs for hemodialysis between AKI patients due to sepsis and non-sepsis, as well as to determine the factors that influence the mortality of patients with AKI.Methods. An analytical observational study was conducted among patients with AKI according to the KDIGO criteria and aged ≥40 years old. Data were obtained from patients’ medical records in Saiful Anwar Hospital Malang in January-June 2019. Patients were categorized into sepsis or non-sepsis group. Patients were then followed during hospitalization for mortality, length of stay, renal recovery, and need of hemodialysis outcome. The difference in the incidence of mortality, renal recovery, and need of hemodialysis between the two groups were analyzed by Chi Square bivariate analysis, while the difference in length of stay was analyzed by Mann Whitney test. Risk factors that influence mortality will be tested by multivariate analysis of binary logistic regressionResults. There were 135 subject consist of 80 (59.25%) subjects of AKI due to sepsis and 55 (40.74%) subjects of AKI non-sepsis. Patients with AKI due to sepsis has higher hospital mortality (p=0.002), increased needs for hemodialysis (p=0.017), low renal recovery (p=0.022), and longer length of stay (p=0.004) compared to non-sepsis. From multivariate analysis, we revealed that the contributing factors for mortality in patients with AKI were sepsis [OR 3.468 (IK 95% 1.438-8.366); p=0.006], oligoanuria [OR 2.923 (IK 95% 0.950-8.990); p=0.041], and decreased of consciousness [OR 3.817 (IK 95% 1.589-9.168); p=0.003].Conclusion. Higher hospital mortality, longer length of stay, increased needs for hemodialysis, and lower renal recovery in patients with AKI due to sepsis compared to those without sepsis. The conditions of sepsis, oligoanuria and decreased of consciousness have a very significant influence on the mortality of AKI patients.